THE MULTIFACTORIAL NATURE OF OCCUPATIONAL STRESS IN HEALTHCARE PROFESSIONALS: A SCOPING REVIEW - Angger Wicaksana; Sugiyani Sugiyani (Adisam Publisher, 2025)
Occupational stress and burnout critically threaten healthcare professionals' (HCPs) well-being and patient care quality, a situation significantly exacerbated post-pandemic. Synthesizing contemporary risk factors is essential for effective interventions. This scoping review systematically maps empirical literature (January 2021-December 2025) identifying the multifactorial determinants of stress and/or burnout among doctors and nurses. Following PRISMA-ScR guidelines, PubMed and Wiley databases were searched. Data from 25 eligible primary research articles in English underwent narrative synthesis and thematic analysis. Analysis confirmed the complex, multifactorial nature of HCP stress/burnout. Four major interconnected themes of risk factors were identified: (1) Workload and Job Demands (quantitative overload like excessive hours, and qualitative pressures including high emotional/cognitive labor); (2) Organizational Factors and Resources (deficits like inadequate staffing/support, low job control, effort-reward imbalance, poor leadership/communication); (3) Individual Factors (demographics, health status, sleep quality, personality traits, coping strategies); and (4) Pandemic Context (unique stressors like infection fear, resource scarcity, ethical dilemmas). The findings highlight a critical interplay between demanding work conditions, inadequate organizational support, individual vulnerabilities, and crisis contexts, underscoring the need for multi-level interventions addressing systemic, organizational, and individual factors to mitigate HCP stress and burnout.